0493 Daytime Sleepiness in Children with Asthma: Is it really the lungs?. (25th May 2022) - Strang, Abigail; Gao, David; Rani, Seema; Pasquale, Frances; Covington, Lauren; Patterson, Freda; Chidekel, Aaron
Abstract: Introduction: Insufficient nocturnal sleep is the most common reason of excessive daytime sleepiness. Children with asthma are at increased risk for sleep disruption secondary to nocturnal respiratory symptoms and medication effects, as well as more common behavioral pediatric sleep challenges. Not yet clear is the relative contribution of asthma severity versus behavioral factors to daytime sleepiness in a sample of children (8-17 years) with asthma. Methods: This survey-based study was conducted in the outpatient pulmonology clinic at Nemours Children's Hospital, Delaware between 2018-2021. Children with asthma were eligible if they had a diagnosis of asthma, spoke English, and did not have a developmental disorder. Participants completed four surveys: Pediatric Daytime Sleepiness Scale (PDSS, higher scores=more sleepiness), Pediatric Quality of Life Inventory (PEDS-QL, higher scores=better quality of life), PROMIS Pediatric Anxiety short form (higher scores=more anxiety symptoms), and an investigator-designed survey assessing sleep-related technology use. Asthma factors (e.g., asthma severity, lung function [FEV1], number of prescribed asthma medications) were obtained from the electronic medical record. Descriptives and multiple regression analyses were conducted to identify asthma severity and behavioral predictors of daytime sleepiness, controlling for demographics. Results: Study participants (N=100) were mean age 12.1 years [SD=2.6], 54% male, and 45% Black. Persistent asthma was common (87%), with a mean of 4.2 (SD=2.5) prescribed asthma medications, and mean FEV1 of 97% (SD=17.8). On behavioral surveys patients scored: PDSS (M=14.13; range=0-31; SD=6.7), PEDS-QL (M=77.38; range=15.6-100; SD=18.6), and PROMIS (M=14.92; range=8-35; SD=7.2). 74% reported cell phone usage within 1 hour of bedtime. Multiple regression models showed that an increased number of prescribed medications (beta=0.168, p=0.042), lower patient-reported quality of life (beta=-0.310, p=0.004), increased anxiety symptoms (beta=0.203, p=0.05) and bedtime cellphone use (beta=0.290, p=0.003) were significantly associated with daytime sleepiness in children with asthma. Conclusion: A greater number of behavioral than asthma severity factors related to daytime sleepiness in children with asthma. Strategies to reduce anxiety and bedtime cellphone use may be plausible behavioral targets to improve sleep in children with asthma. Further research to examine these associations longitudinally, and in children with more severe asthma, is warranted. Support (If Any): None